2005
DOI: 10.1002/ceat.200500158
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Approaches in the Purification of Plasmid DNA for Therapy and Vaccination

Abstract: The need for large scale plasmid DNA purification processes has increased in the last few years due to the rapid evolution of gene therapy and DNA vaccines. Chromatographic purification of plasmid DNA has specific problems which are mostly related to the structural nature of plasmid DNA, the resemblance of plasmid DNA to some impurities, and the lack of capacity and selectivity of the traditional bead adsorbents. In this paper, plasmid DNA purification using chromatographic processes is reviewed. Initially the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
11

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 88 publications
0
22
0
11
Order By: Relevance
“…Commercially available carriers are designed primarily for protein binding rather than large diameter macromolecules and nanoparticles such as pDNA [33]. It has been reported that these large macromolecules are excluded from particle pores smaller than 500 nm.…”
Section: Effect Of Pdna Concentrationmentioning
confidence: 99%
“…Commercially available carriers are designed primarily for protein binding rather than large diameter macromolecules and nanoparticles such as pDNA [33]. It has been reported that these large macromolecules are excluded from particle pores smaller than 500 nm.…”
Section: Effect Of Pdna Concentrationmentioning
confidence: 99%
“…These nucleic acids are non-active admixtures in the preparations of supercoiled p-DNA which may induce immune reactions (Ferreira, 2005;Stadler et al, 2004). We did not study the adsorption of other immunogenic bacteria components such as proteins onto CNTs.…”
Section: Discussionmentioning
confidence: 98%
“…chromosomal DNA and RNAs. These latter forms are immunogenic and therefore their removal is a prerequisite step in preparing pharmacologically pure plasmid DNA for clinical applications (Ferreira, 2005;Stadler et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous plasmid purification protocols including precipitation and chromatographic processes have been developed [2][3][4][5]. Chromatographic methods for plasmid DNA (pDNA) purification are characterized by high selectivity and high resolution (HR), but the stationary phases used for plasmid purification are limited because of the large size of plasmids.…”
Section: Introductionmentioning
confidence: 99%